Beyond the genome—Towards an epigenetic understanding of handedness ontogenesis. (December 2017) - Schmitz, Judith; Metz, Gerlinde A.S.; Güntürkün, Onur; Ocklenburg, Sebastian
Highlights: The molecular determinants of hemispheric asymmetries are not well understood. Studies revealed few genes accounting for a small part of handedness variance. Family studies indicated heritability of up to 0.66. Epigenetic mechanisms were suggested to contribute to this missing heritability. We review non-genetic influences on handedness and possible epigenetic mechanisms. Abstract: Hemispheric asymmetries represent one of the major organizational principles in vertebrate neurobiology, but their molecular determinants are not well understood. For handedness, the most widely investigated form of hemispheric asymmetries in humans, single gene explanations have been the most popular ontogenetic model in the past. However, molecular genetic studies revealed only few specific genes that explain a small fraction of the phenotypic variance. In contrast, family studies indicated heritability of up to 0.66. It has been suggested that the lack of recognizable genetic heritability is partly accounted for by heritable epigenetic mechanisms. Based on recent neuroscientific findings highlighting the importance of epigenetic mechanisms for brain function and disease, we review recent findings describing non-genetic influences on handedness from conception to childhood. We aim to advance the idea that epigenetic regulation might be the mediating mechanism between environment and phenotype. Recent findings on molecular epigenetic mechanisms indicate that particular asymmetries in DNA methylation might affect asymmetric gene expression in the central nervous system that in turn mediates handedness. We propose that an integration of genes and environment is essential to fully comprehend the ontogenesis of handedness and other hemispheric asymmetries.